2016
DOI: 10.1128/iai.00290-16
|View full text |Cite
|
Sign up to set email alerts
|

Poly- N -Acetylglucosamine Production by Staphylococcus epidermidis Cells Increases Their In Vivo Proinflammatory Effect

Abstract: Staphylococcus epidermidis is a commensal bacterium of human skin and mucous membranes (1). The ability to establish biofilms on the surfaces of indwelling medical devices is a major virulence mechanism of this bacterium, which is the most commonly isolated etiological agent of nosocomial infections (2). S. epidermidis biofilm formation involves initial cellular adherence to a surface, followed by intercellular aggregation and accumulation in multilayer cell clusters (1). This process is dependent on adhesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Similar observations have been made from in vivo studies: IL-6, TNF-α, and IL-1β are typically observed in serum in the first hours post-challenge with live or inactivated S. epidermidis (Wakabayashi et al, 1991 ; Simojoki et al, 2011 ; Bi et al, 2015 ; Ferreirinha et al, 2016 ; Qin et al, 2017 ), or in tissue exudates/homogenates from experimental DRI models (Boelens et al, 2000b ; Svensson et al, 2015 ). The regulatory cytokine IL-10 is also present in vivo (Ferreirinha et al, 2016 ) and it has been shown that S. epidermidis inoculation result in higher IL-10 levels compared to P. aeruginosa in an intradermal infection model (Bialecka et al, 2005 ). In a S. epidermidis DRI mouse model it was shown that IL-10 was involved in reducing infection-associated morbidity, with higher levels of pro-inflammatory cytokines and greater weight loss in IL-10 KO animals.…”
Section: Host Interaction With S Epidermidissupporting
confidence: 69%
See 3 more Smart Citations
“…Similar observations have been made from in vivo studies: IL-6, TNF-α, and IL-1β are typically observed in serum in the first hours post-challenge with live or inactivated S. epidermidis (Wakabayashi et al, 1991 ; Simojoki et al, 2011 ; Bi et al, 2015 ; Ferreirinha et al, 2016 ; Qin et al, 2017 ), or in tissue exudates/homogenates from experimental DRI models (Boelens et al, 2000b ; Svensson et al, 2015 ). The regulatory cytokine IL-10 is also present in vivo (Ferreirinha et al, 2016 ) and it has been shown that S. epidermidis inoculation result in higher IL-10 levels compared to P. aeruginosa in an intradermal infection model (Bialecka et al, 2005 ). In a S. epidermidis DRI mouse model it was shown that IL-10 was involved in reducing infection-associated morbidity, with higher levels of pro-inflammatory cytokines and greater weight loss in IL-10 KO animals.…”
Section: Host Interaction With S Epidermidissupporting
confidence: 69%
“…PIA may contribute to innate immune system evasion by promoting generation of complement C5a fragment (Satorius et al, 2013 ; Al-Ishaq et al, 2015 ), inhibiting phagocytes and neutrophil killing (Vuong et al, 2004b , c ), and reducing the activity of AMPs (Vuong et al, 2004b ; Otto, 2006 ). Recently, other studies have reported slightly opposite findings, with PIA-producing bacteria inducing greater inflammatory responses and enhanced phagocytosis (Spiliopoulou et al, 2012 ; Ferreirinha et al, 2016 ), although Spiliopoulou et al did observe reduced killing in PIA-producing strains as discussed elsewhere recently (Nguyen et al, 2017 ). S. epidermidis also produces a second exopolymer, the poly-γ-glutamic acid (PGA), although at comparatively lower levels.…”
Section: S Epidermidis As a Pathogenmentioning
confidence: 86%
See 2 more Smart Citations
“…PNAG is a surface polysaccharide that is a key virulence factor in highly divergent bacterial species 37,38 . A. baumannii PNAG plays a crucial role in biofilm formation 35 .…”
Section: Resultsmentioning
confidence: 99%